The Lotus japonicus ROP3 Is Involved in the Establishment of the Nitrogen-Fixing Symbiosis but Not of the Arbuscular Mycorrhizal Symbiosis - García-Soto, Ivette; Boussageon, Raphael; Cruz-Farfán, Yareni Marlene; Castro-Chilpa, Jesus Daniel; Hernández-Cerezo, Liz Xochiquetzal; Bustos-Zagal, Victor; Leija-Salas, Alfonso; Hernández, Georgina; Torres, Martha; Formey, Damien; Courty, Pierre-Emmanuel; Wipf, Daniel; et al. (Frontiers in Plant Science, 2021)
Legumes form root mutualistic symbioses with some soil microbes promoting their growth, rhizobia and arbuscular mycorrhizal fungi (AMF). A conserved set of plant proteins rules the transduction of symbiotic signals from rhizobia and AMF in a so-called common symbiotic signaling pathway (CSSP). Despite considerable efforts and advances over the past 20 years, there are still key elements to be discovered about the establishment of these root symbioses. Rhizobia and AMF root colonization are possible after a deep cell reorganization. In the model, of legume-rhizobia interaction, Lotus japonicus-Mesorhizobium loti, this reorganization has been shown to be dependent on a SCAR/Wave-like signaling module, including Rho-GTPase (ROP in plants). Here, we studied the potential role of ROP3 in nitrogen-fixing symbiosis (NFS) as well as in arbuscular mycorrhizal symbiosis (AMS). We performed a detailed phenotypic study of the effects of the loss of a single ROP on the establishment of both root symbiosis. Moreover, we evaluated the expression of key genes related to CSSP and to rhizobial-specific pathway. Under our experimental conditions, rop3 showed less nodule formation at 7- and 21-days post inoculation as well as less microcolonies and a higher frequency of epidermal infection threads. However, AMF root colonization was not affected. These results suggest a role of ROP3 as a positive regulator of infection thread formation and nodulation in L. japonicus. In addition, CSSP gene expression was neither affected in NFS nor in AMS condition in rop3. whereas the expression level of some genes belonging to the rhizobial-specific pathway, like RACK1, decreased in NFS. We may suggest that ROP3 is involved in NFS only, and is neither required for intra-radical growth of AMF and arbuscule formation in AMS.